(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: WHO defines health as a state of complete physical, mental, and social well-being. Patients suffering from β-Thalassaemia suffer from a lot of complaints which may be directly or indirectly related to their chronic illness. This also affects their compliance with their medication and their overall feeling of well being. Our study aims to examine factors associated with quality of life among thalassaemia patients. Methods: This study was a cross-sectional analytical study with convenience sampling studying 101 patients 2 years and above with regular follow-up attending the thalassaemia day care center at Sir Ganga Ram Hospital, Lahore from 1st October 2011 to 31st December 2011. Data was collected using a structured questionnaire after getting verbal informed consent from the patient by a trained interviewer; patients less than 10 years of age were assisted by their parents. Results: About 49% of the patients strongly agreed that they were depressed due to their illness and 5% had suicidal ideation and had planned to end their life. Forty two percent patients (> 10 years) had limited activities because of their illness and 26.7% needed the help of other persons with personal care needs and 34.7% patients (> 10 years) required help of others for handling their routine daily activities. About 67% had arthritis, 64.4% had back/neck problem, 52.5% had lung/breathing problem, 25.7% had depression/anxiety/emotional problems, 20.8% had heart problem, 19.8% had fractures/ bone/joint problem, and 17.8% had eye/vision problems. Conclusion: Quality of life issues must be dealt with in order to improve the health and promote multidisciplinary approach in the care of thalassemia patients.